PENGARUH PEMBERIAN KREDIT MODAL KERJA TERHADAP PENDAPATAN PEDAGANG KECIL ( Studi Kasus Pada PD. BPR NTB LOBAR CABANG GUNUNGSARI TAHUN 2018 ) - Suhardi Ansor; Baiq Dewi Lita Andiana (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2020)
This study aims to determine whether there is an influence on the granting of working capital loans to the income of small traders in PD. BPR NTB West Lombok Gunungsari Branch. This type of research is associative research which aims to determine the relationship between two or more variables. The data used in this study are primary data and secondary data. Primary data is data taken directly from the field, while secondary data is data obtained through intermediary media such as books, records, evidence and archives published or not. Data analysis in this study uses validity test, reliability test, normality test, linearity test , simple linear regression test, correlation test and coefficient of determination. Based on the results of the tests that have been carried out, it can be concluded that the granting of working capital loans has a significant influence on the income level of small traders.